Dectin-1 mediates the biological effects of beta-glucans. - Brown, G; Herre, J; Williams, D; Willment, J; Marshall, A; Gordon, S (2003)
The ability of fungal-derived beta-glucan particles to induce leukocyte activation and the production of inflammatory mediators, such as tumor necrosis factor (TNF)-alpha, is a well characterized phenomenon. Although efforts have been made to understand how these carbohydrate polymers exert their immunomodulatory effects, the receptors involved in generating these responses are unknown. Here we show that Dectin-1 mediates the production of TNF-alpha in response to zymosan and live fungal pathogens, an activity that occurs at the cell surface and requires the cytoplasmic tail and immunoreceptor tyrosine activation motif of Dectin-1 as well as Toll-like receptor (TLR)-2 and Myd88. This is the first demonstration that the inflammatory response to pathogens requires recognition by a specific receptor in addition to the TLRs. Furthermore, these studies implicate Dectin-1 in the production of TNF-alpha in response to fungi, a critical step required for the successful control of these pathogens.